What is Possible about China’s Internet Public Domain? - Ren, Ziwei (International Journal of Social Sciences and Public Administration, 2024)
Since the ideal type of "public domain" was proposed by Habermas, it has attracted the attention and research of many Chinese and foreign scholars. In the unique social structure of China. With the development of the Internet, the network public domain has become a new form of the real public domain. In the process of this development, can we keep an optimistic attitude towards the online public domain as in the previous academic research? However, from the actual situation, the performance of the network public domain is far from the theoretical expectation, and there are some alienation phenomena such as the change of the mode of information dissemination, the transformation of public subjects and the transfer of communication power. These become the difficulties that prevent the online public domain from becoming possible.